Frequency of Failure of St-Segment Resolution after Primary Percutaneous Coronary Intervention in Patients with St-Segment Elevation Acute Myocardial Infarction - Muhammad Rahman Khalid, Muhammad Adeel Qamar, Ashok Kumar, Rajesh Kumar, Muhammad Owais, Naveed Ahmed Shaikh, Tahir Saghir, Jawaid Sial, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of failure of ST-segment resolution after primary percutaneous coronary intervention (PCI) in patients with ST-segment elevation acute myocardial infarction (MI). Methodology: This cross-sectional study was carried out at the CCU department of the National Institute of Cardiovascular Diseases (NICVD) Karachi, during six months from January 2017 to July 2017. All patients with ST elevation myocardial infarction admitted at CCC and undergoing primary PCI, the onset of typical pian of chest and related presentation in the last 12 hours that persists at least > 20 minutes, without the previous administration of fibrinolytic therapy assessed with history and previous reports, platelet glycoprotein IIb/IIIa inhibitors without prior administration and of either gender were included. All study subjects were shifted to Angiography department, the arterial sheath was inserted only through to the femoral route to prevent bias, and the interventional cardiologist with a minimum 05 years of professional experience was chosen. Angiography was performed, and the identified occlusion area was by interventional cardiologist ballooned/stented. ST resolution failure was seen after/within 30 minutes of primary angioplasty. All the information was collected via study proforma and SPSS version 26 was used for the data analysis. Results: Mean age of the patients was 56.18±8.70 years, average BMI was 25.56±4.76 kg/m2. Females were 25% and males were 77%. Complete resolution was achieved in 73% patients, while 22% patients Failure of ST-segment resolution post PPCI. Conclusion: Our findings show that ST-segment resolution in the ECG within 30 minutes, as opposed to the traditional 90-min successful PPCI, is a significant predictive predictor. The intriguing discovery that ST-segment resolution has limited predictive value in a cohort of STEMI cases managed by the PPCI deserves additional exploration, especially as it is already widely used as the surrogate end point in trials.